2013
DOI: 10.1080/14613808.2012.712508
|View full text |Cite
|
Sign up to set email alerts
|

TheAccafellows: exploring the music making and culture of a collegiate a cappella ensemble

Abstract: Despite the growth in number and popularity of collegiate a cappella ensembles in the USA over the past 20 years, few researchers have studied these self-governed, student-run, popular music ensembles. This ethnographic case study examined the music making and culture of the Accafellows, an all-male a cappella group at a mid-western American university. An analysis of coded data from individual and group interviews and rehearsal and performance observations revealed five emergent themes: (1) music-making cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…These factors include gender, age, peer influence, stereotypes, and the presence of role models (Raider-Roth, Albert, Bircann-Barkey, Gidseg & Murray, 2008;Shepard, Nicpon, Haley, Lind & Ming Liu, 2011;Frazier, 2012;Henry, 2013;Miranda, 2013;Way, Hernandez, Rogers & Hughes, 2013). Research confirms the strong relationship between musical skill and identity 4 development during the school years and subsequent reengagement in musical activity during the adult years (Creech, Hallam, Varvarigou, Gaunt, McQueen & Pincas, 2013;Paparo, 2013).…”
Section: The Adolescent Male Voice Change Motivation and Identity Dmentioning
confidence: 63%
See 1 more Smart Citation
“…These factors include gender, age, peer influence, stereotypes, and the presence of role models (Raider-Roth, Albert, Bircann-Barkey, Gidseg & Murray, 2008;Shepard, Nicpon, Haley, Lind & Ming Liu, 2011;Frazier, 2012;Henry, 2013;Miranda, 2013;Way, Hernandez, Rogers & Hughes, 2013). Research confirms the strong relationship between musical skill and identity 4 development during the school years and subsequent reengagement in musical activity during the adult years (Creech, Hallam, Varvarigou, Gaunt, McQueen & Pincas, 2013;Paparo, 2013).…”
Section: The Adolescent Male Voice Change Motivation and Identity Dmentioning
confidence: 63%
“…These factors include gender, age, peer influence, stereotypes, and the presence of role models (Raider-Roth, Albert, Bircann-Barkey, Gidseg & Murray, 2008;Shepard, Nicpon, Haley, Lind & Ming Liu, 2011;Frazier, 2012;Henry, 2013;Miranda, 2013;Way, Hernandez, Rogers & Hughes, 2013). Research confirms the strong relationship between musical skill and identity 4 development during the school years and subsequent reengagement in musical activity during the adult years (Creech, Hallam, Varvarigou, Gaunt, McQueen & Pincas, 2013;Paparo, 2013).Other research has explored how adolescents, and adolescent boys in particular, develop conceptions of their future possible selves. These studies suggest that the development of possible selves is developmental and sequential, with six stages that progress from conception of an envisioned future self to realisation of that future self (see Hock, Deshler & Schumaker, 2006;Freer, 2009b).…”
mentioning
confidence: 74%
“…Students and tutors agreed on important skills such as arranging, improvising, and playing-by-ear. While many of the studies seemed to focus on composition for instrumentalists, researchers have found collegiate a cappella choirs benefited from developing skills that allowed them to arrange and compose their own music (Berglin, 2015; Paparo, 2013).…”
Section: Beneficial Experiencesmentioning
confidence: 99%
“…Framed in terms of Achievement Goal Theory, they offered suggestions to promote a learning orientation amongst students (in order to foster motivation) that include: using varied, meaningful, and challenging tasks; emphasizing effort, improvement, and enjoyment rather than competition during evaluation tasks; and providing opportunities for student input and choice ( Green and Hale, 2011 , p. 47). The work considers the learning environment and music-making ‘culture’, which as Paparo (2013) discussed, influence whether and to what degree students are involved in music-making – both in and out of school. Paparo (2013 , p. 35) argued that educators should incorporate practices that “enable students to be autonomous at each level of their development” to assist in promoting life-long musical involvement.…”
Section: Introductionmentioning
confidence: 99%
“…The work considers the learning environment and music-making ‘culture’, which as Paparo (2013) discussed, influence whether and to what degree students are involved in music-making – both in and out of school. Paparo (2013 , p. 35) argued that educators should incorporate practices that “enable students to be autonomous at each level of their development” to assist in promoting life-long musical involvement. It seems that educators should encourage their students to make music beyond the classroom – and to focus on aspects of the classroom program that will promote continued participation as well as promote links to the learning outside of school ( Silveira, 2013 ).…”
Section: Introductionmentioning
confidence: 99%